Monitoring electronic educational and scientific resources using Google Analytics - N. V. Soroko; M. A. Shynenko (Academy of Cognitive and Natural Sciences, 2013)
Currently, many scientific resources are created electronically. Such resources include: documents; electronic publications; electronic catalogs; pictures and images in different formats; audio, video, animation; digital maps and cartographic materials; computer programs, etc. It becomes important to analyze their relevance and the need for the development of science and education. Therefore, the problem of monitoring these resources arises. Google Analytics is a product of Google, which is part of the services called "cloud computing" (Cloud Computing). Cloud Computing is a data processing technology in which a software tool is provided to the user as an Internet service. For example, Google Analytics is a free service offered to create detailed statistics of website visitors.